The Relationship between Self-Efficacy, Self-Care Behavior, and Generalized Anxiety Disorder in COVID-19: A Path Analysis Model - Mohammad Hossien Delshad; Fahimeh Pourhaji; Fatemeh Pourhaji; Hassan Azhdari Zarmehri (Diponegoro University, 2022)
Background: The outbreak of the COVID-19 pandemic has a strong impact on individuals and becomes a very stressful period. Long-term exposure to stress due to lockdown scenario may also increase psychological distress by reducing support resources, and in these circumstances, personal resources such as self-efficacy and its relationships appear important. It is important to explore people's beliefs about their capabilities to produce designated levels of behavior in the face of COVID-19, which is not known in the target population, and also to show its effect on anxiety. Purpose: This study aimed to investigate the relationship between self-efficacy, self-care behavior, and generalized anxiety disorder in COVID-19. Methods: A cross-sectional online survey was performed after COVID-19 was confirmed in Iran. The samples of the study were 500 residents in the Razavi Khorasan province, Iran, that were randomly selected. Demographic data, general self-efficacy, self-care behavior, and the Generalized Anxiety Disorder (GAD-7) questionnaires were used for data collection. The data were analyzed using bivariate correlation and hierarchical linear regression models. Results: The mean(SD) age of the participants was 31.9(11.9). Their GAD-7 scores had severe anxiety (score ≥17). There was a negative and significant relationship between generalized anxiety disorder and self-efficacy (r=-0.238, p≤0.01). Also, there was a positive and significant relationship between self-efficacy and self-care behavior. No significant relationship between generalized anxiety disorder and self-care behavior was found. The path analysis model estimated anxiety and self-efficacy as about 4% of the variance self-care behavior in COVID-19. Conclusion: This study revealed that enhancing self-efficacy levels might reduce anxiety. Self-efficacy-enhancing programs should be used as part of the routine readiness effort drives and health care system change.